How Do Personality Traits Effect Shame and Guilt?: An Evaluation of the Turkish Culture - AKBAĞ, MÜGE; ERDEN ÇINAR, SEVAL (ANI YAYINCILIK, 2015)
Problem Statement: Feelings of shame and guilt as negative social emotions have a deep and continuous impact throughout our lives, particularly on our behaviors in both intrapersonal and interpersonal relationships. It was widely accepted that these feelings originate from a person's early period of life's interpersonal experiences in the family and other key relationships. According to literature, shame and guilt are also related to personality traits; however, research findings were not consistent with each other. At this point, owing to the possible effect of the culture on shame and guilt, it can be considered that the relationship between these emotions and personality needs to be investigated in the cultural context. Purpose of the Study: The aim of the present study is to investigate the predictive power of the Big Five Model's personality traits on shame and guilt in Turkish culture. Methods: The study was designed according to the Relational Survey Model. The sample of the study consisted of 360 (F=183, M=177) students who studied in several faculties and departments of a city university located in the western part of Turkey. The participants' age ranged between 1730 years (M=21.35, SD=1.64). The Shame-Guilt Scale and Five-Factor Personality Inventory (NEO FFI) were used as measurements. Findings and Results: Results showed that shame and guilt were predicted by personality traits. In terms of shame, it was found that neuroticism had the largest effect on both genders. The greater the scores were for neuroticism, the greater was shame. Shame was also predicted by openness to experience for both genders, negatively. Moreover, the results revealed that shame was predicted by conscientiousness and agreeableness among only women. We also determined that guilt was predicted by agreeableness for both genders, but was predicted by conscientiousness among only men. Conclusions and Recommendations: In conclusion, personality traits play a key role in the formation of individuals' shame and guilt. However, the predictive power of personality traits were differentiated in terms of gender, and the findings should be discussed in a cultural context. The findings of the study give clear evidence that besides personality traits based on biological origins, cultural context also has an impact on the development of these feelings. Therefore, the cultural meanings and construction of both these feelings and personality traits should be clearly defined by conducting quantitative research besides qualitative research for further studies.
Keywords: Shame; guilt; Big Five personality traits; personality development; Turkish culture; 5-FACTOR MODEL; BIG 5; VALIDATION; ASSOCIATIONS; RESPONSES; GENDER